PERMINTAAN BERAS DI INDONESIA: REVISITED - Sugiyanto, Catur (Journal of Indonesian Economy and Business, 2006)
This paper examines the demand for rice in Indonesia. The data used are timeseries data, ranges between 1970 and 2003, and data from National Survey (SUSENAS)2003. We employ the Almost Ideal Demand System (AIDS) and its inverse to model theIndonesian demand for rice. We also estimate single equation, both ordinary and inversedemand models. Las but not least, the Error Correction Mechanism is used to model thedemand. However, the single (ordinary) equation model outperforms the others.The demand for rice in Indonesia has some regular behaviour, negative withrespect to price and positive in line with the income. However, the magnitudes of theparameters, the elasticity, have been changing. The elasticity with respect to income isdecreasing, indicates that rice is becoming an inferior goods. Family whose expendituresare lesser than 300,000 Rupiahs per month will increase their rice consumption inresponse to the increase in their income. The changes in the elasticity and the variabilityof the consumption in response to income make difficult to predict the total demand forrice.Keywords: Indonesia, rice, demand, AIDS/IAIDS